1983
DOI: 10.1159/000123547
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Short-Term Cold-Induced TRH Release in the Median Eminence of Unanesthetized Rats

Abstract: IR-TRH release in the median eminence was directly estimated in conscious rats during the first 130 min of exposure to cold (4 °C), using a push-pull cannulation. A three-fold increase in IR-TRH release was observed, with a peak of 10.00 ± 2.19 pg/15 min occurring 40 min after exposure to cold; control rats, left at 24 °C, stayed at the baseline secretion rate of 3.40 pg/15 min which was the sensitivity limit of the RIA assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 15 publications
0
44
1
2
Order By: Relevance
“…Although it would seem surprising that a presumptive endocrine factor is strongly expressed in an exocrine gland, there have been numerous reports of other growth factors being expressed in salivary glands (15)(16)(17)(18)(19), and it has been shown that endocrine factors expressed after introduction of DNA into these glands are readily secreted into the bloodstream (20,21). Indeed, a body of opinion contends that salivary glands have a mixed exocrine and endocrine function (22)(23)(24). Similarly, we also saw expression in the lacrimal glands of newborn mice.…”
Section: Resultsmentioning
confidence: 99%
“…Although it would seem surprising that a presumptive endocrine factor is strongly expressed in an exocrine gland, there have been numerous reports of other growth factors being expressed in salivary glands (15)(16)(17)(18)(19), and it has been shown that endocrine factors expressed after introduction of DNA into these glands are readily secreted into the bloodstream (20,21). Indeed, a body of opinion contends that salivary glands have a mixed exocrine and endocrine function (22)(23)(24). Similarly, we also saw expression in the lacrimal glands of newborn mice.…”
Section: Resultsmentioning
confidence: 99%
“…TRH gene expression in the PVN is strictly controlled by the feedback action of thyroid hormones (Koller et al 1987, Segerson et al 1987b, Rondel et al 1988, Hollenberg et al 1995, Satoh et al 1999 and is regulated in multiple physiological conditions including: circadian and estrous cycles (Covarrubias et al 1988, Uribe et al 1991, suckling and weaning (Uribe et al 1993, 1995b, Sánchez et al 2001, cold stress (Zoeller et al 1990, Uribe et al 1993, Sánchez et al 2001 and fasting (Blake et al 1991, Legradi et al 1997a, Fekete et al 2002. In addition, a fast and transient increase in proTRH mRNA levels in the PVN (maximal at 30-60 min) is produced by cold exposure or suckling (Uribe et al 1993, Sánchez et al 2001, conditions that activate TRH release from the median eminence (Arancibia et al 1983, de Greef et al 1987, Rondel et al 1988.…”
Section: Introductionmentioning
confidence: 99%
“…As CART is the only known peptide that coexists with TRH in the PVN (Fekete et al, 2000) it is feasible that under the appropriate circumstances, the genes for both peptides may become simultaneously activated. The paradigm of the lactating rat subject to either suckling or cold exposure, conditions when TRH neurons are rapidly activated in the PVN (Sánchez et al, 2001), exemplify in vivo situations where TRH is released but the secretion of TSH and prolactin diverge (Adels et al, 1986;Arancibia et al, 1983;de Greef and Visser, 1981;Sanchez et al, 2001;van Haasteren et al, 1996). Using this paradigm, we demonstrate herein a differential activation of CART neurons in the PVN, stimulated by cold exposure but not by suckling.…”
Section: Discussionmentioning
confidence: 63%
“…Included among the physiologic stimuli associated with activation of hypophysiotropic TRH neurons are suckling and cold exposure that induce TRH release (Arancibia et al, 1983;de Greef and Visser, 1981;Fink and Ben-Aroya, 1983;Hefco et al, 1975) and a rapid (30-60 min) and transient increase in proTRH mRNA levels in the PVN (Rage et al, 1994;Sanchez et al, 2001;Uribe et al, 1993;van Haasteren et al, 1996). However, the response of pituitary target cells is specific to the stimulus.…”
Section: Introductionmentioning
confidence: 99%